Mothers, fathers and the intergenerational transmission of gender ideology - Perales, Francisco; Hoffmann, Heidi; King, Tania; Vidal, Sergi; Baxter, Janeen (My University, 2021)
Traditional gender beliefs play an important role in (re-)producing gender inequalities, and trends towards gender egalitarianism have stalled. As such, identifying factors that contribute to individuals upholding traditional versus egalitarian gender attitudes is an important scholarly endeavour. While previous studies have identified critical predictors-such as religion, education and parenthood-intergenerational influences have received comparatively little empirical attention. Drawing upon gender-socialization theory, we derive hypotheses about how parental attitudes towards gender are transmitted to their children, considering differences between mothers' and fathers' influences, parental (dis)agreement in attitudes, and moderation by child's gender. We test these hypotheses using high-quality data from a national sample of Australian 14/15-year-old adolescents (Longitudinal Study of Australian Children, n = 1806). We find substantial intergenerational associations in gender ideology. Paternal and maternal attitudes exert a similar degree of influence on their children's attitudes, and have complementary rather than cumulative effects. While fathers' attitudes influence sons' and daughters' attitudes equally, mothers' attitudes influence daughters' attitudes more than sons'.
Social Science Research
Keywords: Attitudes; Australia; Families; Gender; Intergenerational transmission; Socialization; Gender; Identity; Intergenerational transfer